Motor cortex inhibition by TMS reduces cognitive non-motor procedural learning when immediate incentives are present. (December 2017) - Wilkinson, Leonora; Koshy, Philip J.; Steel, Adam; Bageac, Devin; Schintu, Selene; Wassermann, Eric M.
Abstract: Inhibitory repetitive transcranial magnetic stimulation (rTMS) of the primary motor area (M1) impairs motor sequence-learning, but not basic motor function. It is unknown if this is specific for motor forms of procedural learning or a more general effect. To investigate, we tested the effect of M1-inhibition on the weather prediction task (WPT), a learning task with minimal motor learning component. In the WPT, participants learn arbitrary, probabilistic, associations between sets of meaningless cues and fictional outcomes. In our "Feedback" (FB) condition, they received monetary rewards/punishments during learning. In the "paired associate" (PA) condition they learned the same information by passive observation of associations. The observational and feedback learning conditions were matched for their non-learning-specific motor demands. In each of two FB or PA sessions, we delivered Real (inhibitory) or Sham continuous theta-burst (cTBS) to the left-M1, before 150 training-trials. We then tested learning with 42 trials without feedback immediately after learning and again 1-h after cTBS. Compared to Sham, Real cTBS reduced performance during FB-learning, when learning was immediately reinforced, but not when knowledge was tested after PA learning. Furthermore, when FB-based memory was tested after learning without immediate incentive, there was no effect of TMS compared to post-PA test performance, showing the TMS effect operated only in the presence of incentive and feedback. We conclude that M1 is a node in a network underlying feedback-driven procedural learning and inhibitory rTMS there results in decreased network efficiency.